Rheological properties of polymer colloid–cellulose thickener systems - Sviderskyi, Valentyn; Melnyk, Liubov; Shendera, Anna; Fleisher, Hanna (Lviv Politechnic Publishing House, 2018)
Запропоновано спосіб модифікації полі- мерних водних дисперсій за допомогою загусників, а саме естерів целюлози. Досліджено вплив природи плівко- утворюючого агенту на реологічні властивості системи за різного ступеню деформації зсуву. Визначено структурно- механічні та реологічні властивості досліджуваних систем. Встановлено, що гідроксиетилцелюлоза є кращим загусником у порівнянні з карбоксиметилцелюлозою. Гідроксиетилцелюлоза надає двокомпонентним системам більш чітко визначені псевдопластичні властивості, що полегшує виробництво та застосування фарб. Результати дослідження можуть бути використані при виробництві водоемульсійних лакофарбових покриттів

An approach to water emulsions modification with structure forming additives, namely cellulose esters, is proposed in the article. Influence of the film former origin on the system rheological properties at different shear-strain rates was examined. Structural and mechanical, as well as rheological properties of the studied systems were determined. The results confirm that hydroxyethylcellulose has a greater structure forming effect in comparison with carboxymethylcellulose. Hydroxyethylcellulose provides well-definite pseudoplastic properties to the two-component systems that facilitate the production and application of paints. The results of the investigation could be used in the emulsion paint (coatings) production.
Реологічні властивості системи водна дисперсія полімеру–целюлозний загусник
Keywords: реологічні властивості; в’язкість; водна дисперсія полімеру; естер целюлози; структурно- механічні властивості; rheological properties; viscosity; polymer colloids; cellulose esters; structural and mechanical properties